2010
DOI: 10.1007/978-1-4419-5913-3_49
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach for Computing the Active Site of the Ribonucleoside Hydrolase of E. coli Encoded by rihC

Abstract: We predict the potential active and catalytic sites, the transition state and how it is stabilized, and the mechanism of rihC ribonucleoside hydrolase of E. coli. Our approach is based on well-known primary sequence analysis techniques. A canonically associated extreme value distribution is used to assess the significance of the prediction. Parameters for the extreme value distribution are computed directly from data. Our practical approach is consistent with known results in the literature. We obtain BLOSUM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Besides, high purity, LA can be obtained by furfuralcohol hydrolysis with a suitable solvent and catalyst. Considerable research over the past years has focused on the catalytic conversion of biomass into LA by both batch processes and continuous technology 14–16…”
Section: Introductionmentioning
confidence: 99%
“…Besides, high purity, LA can be obtained by furfuralcohol hydrolysis with a suitable solvent and catalyst. Considerable research over the past years has focused on the catalytic conversion of biomass into LA by both batch processes and continuous technology 14–16…”
Section: Introductionmentioning
confidence: 99%
“…18 A number of catalysts for the conversion of LA to GVL have been reported in the literature. 13,[19][20][21][22][23] In general the catalytic systems for GVL synthesis from LA consist of noble metal catalysts (Ru, Au, Pt, Pd) and non-noble metal catalytic systems (Cu, Ni). Ru/C is, by far, the most-reported catalyst for this reaction 24 and has shown outstanding performance in the aqueous phase at mild temperature and pressure (130 °C, 12 bar H 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[14] Extensive studies have been reported on the conversion of biomass feedstock to levulinic acid using homogeneous catalysts, including mineral acids and metal chlorides. [15][16][17][18][19] An overview of levulinic acid synthesis using various feedstocks and acid catalysts is given by Girisuta, [20] as well as by Rackemann and Doherty. [21] We have developed a kinetic model for aqueous-phase production of levulinic acid from glucose using a homogeneous acid catalyst.…”
Section: Introductionmentioning
confidence: 99%